Apocalyptic Propaganda: How the U.S. Government Manufactured Consent on The War on Terror - Blom, Carin; Lindgren, Tomas (Al-Albab, 2023)
War and propaganda have been linked together for a long time because of a natural human inhibition against killing other humans. To get citizens to give their consent to go to war and kill, the leader(s) need to influence them. The aim of this study is to analyse the content and functions of the U.S. governments post 9/11 propaganda to find out how this where done. Coyne and Hall argue that propagandists need the publics enlighted consent to be able to influence them. This work will prove that the U.S. government used propagandistic tools, like the fear of our own and our civilizations annihilation through an apocalyptic language, to circumvent our rational thinking and talk unbridled to our emotions and thereby inhibit our higher cognitive functions. As method we use bricolage. Bricolage interpretations adapt different technical discourses to each other and move freely between different techniques and concepts. In this work it had an advancement over other methods because our field of investigation stretched over different fields of research and we were free to use the method that best suited our collected data. We demonstrate that the U.S. government functioned as fearmongers on their home audience to stir up emotions so the citizens would choose the path that best suited the leader(s), but that it was far from being enlighted.